The taste of scales and chords - Taitz, Alan; Shalom, Diego; Trevisan, Marcos; Mesz, Bruno (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
Reliable crossmodal correspondences between basic tastes and music features have been found in recent studies [1,2]. In this work, we explore associations between scales, chords and tastes. Several of these elementary musical structures show non-random patterns of matching with basic tastes. Moreover, their aggregate dyadic consonance [3] anti-correlates with the relative frequency of their matching to bitter taste.